A comparative analysis of initiatives and adaptation measures to climate change undertaken in Poland and Western Europe - Dorota Michalak (Comparative Economic Research. Central and Eastern Europe, 2016)
Climate change is one of the greatest contemporary threats to our planet's environmental, social and economic well-being, accompanied by major changes in life support systems on Earth, where the far-reaching effects will be felt in the coming decades. The Earth's climate is warming rapidly due to emissions of greenhouse gases caused by human activities such as burning fossil fuels and deforestation. The Stern Report predicts that in the long term, climate change could cut global gross domestic product (GDP) by 5 to 20% or more each year if it is not brought under control by reducing greenhouse gas emissions. The purpose of this paper is to compare the degree of influence of climate change on the economies of Western Europe and comparing national strategies for adaptation to climate change in selected countries of Western Europe and Poland. The analysis of the main initiatives for adaptation to climate change in selected countries of Western Europe and Poland relate to key issues mentioned in the strategic documents of the European Commission. In the United Kingdom the main emphasis is on the reduction of greenhouse gases as a form of preventive action, rather than adaptation to climate change. All strategies recognize the importance of raising public awareness about the negative effects of climate change and the importance of preparing adaptation measures, and stress the need to support the critical and most sensitive sectors of the European economy - forestry, agriculture and fisheries. The Polish strategy of adaptation to climate change does not deviate from the strategy of these countries of Western Europe, but it must be emphasized that this is only a document listing recommendations on the scope of operations of adaptation to climate change. Its realization is a separate issue.
Keywords: 330; climate change; forecasts and costs of climate change; adaptation to climate change